Plantar pressures in the tennis serve - Girard, O.; Eicher, F.; Micallef, J. P.; Millet, G. (Journal of Sports Sciences, 2010)
In-shoe loading patterns were examined in each foot (back and front) separately during two types of tennis serve [first (or flat) and second (or twist) serve] and two service stance styles [foot-up (back foot is moved forward next to front foot for push-off) and foot-back (feet remain at the same relative level)]. Ten competitive tennis players completed five trials for each type of serve and service stance style in random order. Plantar pressure distribution was recorded using Pedar insoles divided into nine areas for analysis. Mean and peak pressures (+15.2%, P < 0.01 and +12.8%, P < 0.05) as well as maximal forces (+20.2%, P < 0.01) were higher under the lateral forefoot of the front foot in first than in second serves, while mean forces were higher (+17.2%, P < 0.05) under the lesser toes. Relative load was higher on the lateral forefoot (+20.4%, P < 0.05) but lower (-32.5%, P < 0.05) on the medial heel of the front foot with foot-up compared with foot-back stance. Using a foot-up stance, loading of the back foot was higher (+31.8%, P < 0.01) under the lateral mid-foot but lower (-29.9%, P < 0.01) under the medial forefoot. The type of serve and the stance style adopted have a significant effect on foot loading. Such findings might help improve mechanical efficiency of the serve.